JEL Classification System (Journal of Economic Literature, 2004)
The categories listed below are used to classify books, book reviews, journal articles, and dissertations indexed in JEL and EconLit. The list details the full three-digit classifications used to index journal articles in JEL on CD, EconLit, and e-JEL on www.e-JEL.org . The Annotated Listing of New Books printed in this issue uses the bold face one- and two-digit classifications; the Book Reviews in each issue and the Doctoral Dissertations List printed in December appear under the on-digit classification headings. Please note that books, book reviews, and dissertations are indexed in EconLit using the full three-digit classifications. Those who classify papers or dissertations should choose the most appropriate three-digit classification. New changes to classification system appear as soon as possible on www.AEAweb.org .